T Regulatory Cells and Priming the Suppressive Tumor Microenvironment - Paluskievicz, Christina M.; Cao, Xuefang; Abdi, Reza; Zheng, Pan; Liu, Yang; Bromberg, Jonathan S. (Frontiers in Immunology, 2019)
Treg play a central role in maintenance of self tolerance and homeostasis through suppression of self-reactive T cell populations. In addition to that role, Treg also survey cancers and suppress anti-tumor immune responses. Thus, understanding the unique attributes of Treg-tumor interactions may permit control of this pathologic suppression without interfering with homeostatic self-tolerance. This review will define the unique role of Treg in cancer growth, and the ways by which Treg inhibit a robust anti-tumor immune response. There will be specific focus placed on Treg homing to the tumor microenvironment (TME), TME formation of induced Treg (iTreg), mechanisms of suppression that underpin cancer immune escape, and trophic nonimmunologic effects of Treg on tumor cells. Keywords: Treg, Immunosuppression, Tumor Microenvironment, Metastasis, Anti-tumor immunity